2016
DOI: 10.1128/jvi.03136-15
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Entry Pathway Mediated by the Human Endogenous Retrovirus K Envelope Protein

Abstract: Endogenous retroviruses (ERVs), the majority of which exist as degraded remnants of ancient viruses, comprise approximately 8% of the human genome. The youngest human ERVs (HERVs) belong to the HERV-K(HML-2) subgroup and were endogenized within the past 1 million years. The viral envelope protein (ENV) facilitates the earliest events of endogenization (cellular attachment and entry), and here, we characterize the requirements for HERV-K ENV to mediate infectious cell entry. Cell-cell fusion assays indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 60 publications
5
27
0
Order By: Relevance
“…As a control, sucrose also prevented the endocytic uptake of Alexa Fluor 488-labeled transferrin into both C10 and CHO-HVEM cells (Fig 5I). As expected, sucrose did not inhibit entry of VSVΔG-PIV5 into either cell line because PIV5 enters by fusion at the plasma membrane (31), thus serving as a negative control (Fig 5D, H). Entry of VSV occurs by an endocytic route (3739), and, accordingly, sucrose blocked entry of VSVΔG-G into C10 cells (Fig 5C).…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…As a control, sucrose also prevented the endocytic uptake of Alexa Fluor 488-labeled transferrin into both C10 and CHO-HVEM cells (Fig 5I). As expected, sucrose did not inhibit entry of VSVΔG-PIV5 into either cell line because PIV5 enters by fusion at the plasma membrane (31), thus serving as a negative control (Fig 5D, H). Entry of VSV occurs by an endocytic route (3739), and, accordingly, sucrose blocked entry of VSVΔG-G into C10 cells (Fig 5C).…”
Section: Resultssupporting
confidence: 70%
“…VSVΔG-G is VSVΔG pseudotyped in trans with native VSV glycoprotein G and is known to enter susceptible cells by a clathrin-mediated endocytosis (CME) (30). VSVΔG-PIV5 is VSVΔG pseudotyped with entry glycoproteins HN and F from parainfluenza virus 5 (PIV5), which enters susceptible cells by fusion at the plasma membrane (31) just as PIV5 itself. Both VSVΔG-G and VSVΔG-PIV5 pseudotypes infected all 9 tested cell lines, with varying efficiency (Fig 2C, D), which suggested that limited tropism of VSVΔG-BHLD pseudotype cannot be explained by VSV particle morphology or some other aspect of VSV biology.…”
Section: Resultsmentioning
confidence: 99%
“…1A). Robust incorporation was achieved without substituting the native 109-amino-acid cytoplasmic domain of gB for the 29-amino-acid cytoplasmic tail of VSV-G, a strategy that is often used to improve incorporation of challenging glycoproteins (29,30). The presence of HSV-1 gB in VSV⌬G-gB preparations was verified by Western blotting with anti-gB PAb R68 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Prepared pseudotyped virions were free from contamination with residual VSV-G from helper virus as judged by SDS-PAGE, Western blotting, and the inability of the neutralizing anti-VSV-G antibody to block VSV⌬G-BHLD infectivity. Successful incorporation of heterologous glycoproteins into VSV particles often requires that their cytoplasmic tail be replaced with that of VSV-G (29,30). But the incorporation of gB into the pseudotyped virions was robust and comparable to that of native VSV-G despite the presence of a relatively large cytoplasmic domain.…”
Section: Discussionmentioning
confidence: 99%
“…These variants map to frameshift and missense mutations in the putative envelope protein of this virus (Q779_gp1, also called 'env'). Studies have shown that this envelope protein mediates infections of cells [67]. HERV K113 is a provirus and is capable of producing intact viral particles [68].…”
Section: Comparing 'Dead' and 'Alive' Samples In The Hepb Subgroup Usmentioning
confidence: 99%